Pengaruh Penambahan Puree Labu Kuning (Cucurbita moschata) Terhadap Karakterisitik Siomay Udang - Candra Utami, Ni Putu; Mayun Permana, I Dewa Gede; Selamet Duniaji, Agus (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2021)
This study aims to determine the effect of adding puree of pumpkin on the characteristics of shrimp dumplings and to determine the appropriate addition puree of pumpkin to produce shrimp dumplings with the best characteristics. The experimental design used in this study was a completely randomized design (CRD) consisting of 5 treatments, namely 0%, 10%, 20%, 30%, and 40%. All treatments were repeated 3 times in order to obtain 15 experimental units. The data obtained were analyzed by means of variance and if the treatment had a significant effect, then proceed with the Duncan Multipe Range Test (DMRT). The results showed that the addition of pumpkin pulp had a very significant effect on moisture content, crude fiber content, total ?-carotene, and antioxidant activity using the ?-Bleaching method. Has no significant effect on ash content, hedonic test on color, aroma, texture, taste, overall acceptance, and scoring test on color and texture. The addition of pumpkin pulp 40% had the best characteristics with water content of 61.22%, ash content of 2.59%, crude fiber content of 1.96%, total ?-carotene 0.98 mg / 100 g and antioxidant activity of 5.31%. , by the criteria of yellow color and liked, flavor liked, chewy texture and liked, taste liked and overall acceptance liked.